Fibroblast growth factor 21 is expressed and secreted from skeletal muscle following electrical stimulation via extracellular ATP activation of the PI3K/Akt/mTOR signaling pathway - Arias-Calderón, Manuel; Casas, Mariana; Balanta-Melo, Julián; Morales-Jiménez, Camilo; Hernández, Nadia; Llanos, Paola; Jaimovich, Enrique; Buvinic, Sonja (Frontiers in Endocrinology, 2023)
Fibroblast growth factor 21 (FGF21) is a hormone involved in the regulation of lipid, glucose, and energy metabolism. Although it is released mainly from the liver, in recent years it has been shown that it is a “myokine”, synthesized in skeletal muscles after exercise and stress conditions through an Akt-dependent pathway and secreted for mediating autocrine and endocrine roles. To date, the molecular mechanism for the pathophysiological regulation of FGF21 production in skeletal muscle is not totally understood. We have previously demonstrated that muscle membrane depolarization controls gene expression through extracellular ATP (eATP) signaling, by a mechanism defined as “Excitation-Transcription coupling”. eATP signaling regulates the expression and secretion of interleukin 6, a well-defined myokine, and activates the Akt/mTOR signaling pathway. This work aimed to study the effect of electrical stimulation in the regulation of both production and secretion of skeletal muscle FGF21, through eATP signaling and PI3K/Akt pathway. Our results show that electrical stimulation increases both mRNA and protein (intracellular and secreted) levels of FGF21, dependent on an extracellular ATP signaling mechanism in skeletal muscle. Using pharmacological inhibitors, we demonstrated that FGF21 production and secretion from muscle requires the activation of the P2YR/PI3K/Akt/mTOR signaling pathway. These results confirm skeletal muscle as a source of FGF21 in physiological conditions and unveil a new molecular mechanism for regulating FGF21 production in this tissue. Our results will allow to identify new molecular targets to understand the regulation of FGF21 both in physiological and pathological conditions, such as exercise, aging, insulin resistance, and Duchenne muscular dystrophy, all characterized by an alteration in both FGF21 levels and ATP signaling components. These data reinforce that eATP signaling is a relevant mechanism for myokine expression in skeletal muscle.